Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Game Android Menggunakan Metode Scrum - Lendy Rahmadi; Kusnita Yusmiarti (Prosiding SISFOTEK, 2025)
This study aims to develop an interactive mathematics learning media based on an Android educational game using the Scrum method at SD N 2 Pajar Bulan. The research background arises from the lack of students' interest and motivation in learning mathematics, especially in understanding basic arithmetic concepts. By implementing the Scrum development method, this learning media is designed to create a fun and interactive learning experience. The research was conducted on first and second-grade students and focused on basic mathematical operations such as addition and subtraction. The process of developing the game-based learning media follows three main stages: pregame, game, and postgame. The result of this research is an interactive learning media application that can help students better understand mathematical materials and increase their learning motivation and engagement. This study also identifies challenges in the development and implementation process of the media within the school environment. Through the use of interactive educational games, it is expected that the quality of mathematics learning can improve significantly.